Evaluation of the Technical Assistance Provided by the International Monetary Fund. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2005)
Technical assistance is one of the key services provided by the IMF to member countries-particularly lower income countries. It covers a wide set of activities, from technical assistance to support IMF policy advice to longer-term assistance to support countries' institutional development. This evaluation report examines the relevance and effectiveness of IMF technical assistance, and derives recommendations for both IMF management and the Executive Board.